2002
DOI: 10.1105/tpc.006106
|View full text |Cite
|
Sign up to set email alerts
|

Centromeric Retroelements and Satellites Interact with Maize Kinetochore Protein CENH3

Abstract: Maize centromeres are composed of CentC tandem repeat arrays, centromeric retrotransposons (CRs), and a variety of other repeats. One particularly well-conserved CR element, CRM, occurs primarily as complete and uninterrupted elements and is interspersed thoroughly with CentC at the light microscopic level. To determine if these major centromeric DNAs are part of the functional centromere/kinetochore complex, we generated antiserum to maize centromeric histone H3 (CENH3). CENH3, a highly conserved protein that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
378
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 355 publications
(390 citation statements)
references
References 65 publications
10
378
0
2
Order By: Relevance
“…Investigation of sequences other than the transposable elements and CentO repeats within the central region indicated that they were either unique or low-copy elements. It has been demonstrated that the CentO repeat is located on the functional domain of rice centromere, and the CentC and CRM sequences interact with maize kinetochore protein centromeric histone H3 (CENH3; Cheng et al, 2002;Nagaki et al, 2003;Zhong et al, 2002). Although further studies are needed Ā± including sequence analysis of the gap region Ā± the close association of CentO and RIRE7 sequences observed here emphasizes that these sequences would be the most important essential components for characterizing the centromere structure as functional.…”
Section: Discussionmentioning
confidence: 61%
“…Investigation of sequences other than the transposable elements and CentO repeats within the central region indicated that they were either unique or low-copy elements. It has been demonstrated that the CentO repeat is located on the functional domain of rice centromere, and the CentC and CRM sequences interact with maize kinetochore protein centromeric histone H3 (CENH3; Cheng et al, 2002;Nagaki et al, 2003;Zhong et al, 2002). Although further studies are needed Ā± including sequence analysis of the gap region Ā± the close association of CentO and RIRE7 sequences observed here emphasizes that these sequences would be the most important essential components for characterizing the centromere structure as functional.…”
Section: Discussionmentioning
confidence: 61%
“…Centromeres are regions with lower recombination frequency (Beadle, 1932;Clarke and Carbon, 1980) and often exhibit interspersion of satellite sequences and TEs, as in cereals (Zhong et al, 2002), Arabidopsis (Copenhaver et al, 1999), insects (Sun et al, 2003) and fungi (Cambareri et al, 1998). There are indications of the evolutionary link between the centromere structure and TE's activity: centromeric satellite repeats may arise from DNA transposons (Kapitonov and Jurka, 1999).…”
Section: Processes Acting In Regions Of Reduced Recombinationmentioning
confidence: 99%
“…Maize centromeres contain arrays of two intermingled repetitive DNA elements, including a 156-bp satellite repeat CentC (Ananiev et al 1998) and a centromeric retrotransposon CRM (Zhong et al 2002). The CentC/CRM arrays span several megabases of DNA in some maize centromeres (Jin et al 2004;Ananiev et al 2009).…”
Section: Mapping the Cenh3-binding Domain Of Neom3 (Ncenm3 )mentioning
confidence: 99%